Patient perception of mobile phone apps for the care and prevention of sexually transmitted diseases: cross-sectional study - Jakob, Lena; Steeb, Theresa; Fiocco, Zeno; Pumnea, Teodora; Jakob, Sophia Nomi; Wessely, Anja; Rothenberger, Christoph Clemens; Brinker, Titus Josef; French, Lars Einar; Berking, Carola; Heppt, Markus V. (JMIR mhealth and uhealth, 2020)
Background: In the emerging era of digitalization and electronic health, various health-related apps have been launched, including apps for sexually transmitted diseases. Until now, little has been known about how patients perceive the value of such apps. - Objective: To investigate patient’s attitudes and awareness toward sexually transmitted disease-related apps in an outpatient sexually transmitted disease clinic setting. - Methods: A cross-sectional study was conducted at a dermatovenereological outpatient unit between April and July 2019. Patients completed a self-administered questionnaire on their perceptions of the popularity and usefulness of sexually transmitted disease-related apps. Descriptive analysis was performed with expression of categorical variables as frequencies and percentages. For continuous variables, the median, range, and interquartile range were indicated. Contingency tables and chi-square tests were used to investigate associations between sociodemographic data and items of the questionnaire. - Results: A total of 226 patients were surveyed (heterosexual: 137/193, 71.0%; homosexual: 44/193, 22.8%; bisexual: 12/193, 6.2%); 11.9% (27/225) had previously used health-related apps. Nearly half of the patients (97/214, 45.3%) specifically considered sexually transmitted disease-related apps useful, 47.8% (100/209) voted that they could supplement or support the consultation of a physician. Interestingly, only 35.1% (74/211) preferred a printed patient brochure on sexually transmitted diseases over downloading and using an app, but 64.0% (134/209) would download a sexually transmitted disease-related app recommended by their physician. General information regarding sexually transmitted diseases (93/167, 55.7%), evaluation of skin diseases based on photos or videos (78/167, 53.3%), information on the prevention of sexually transmitted diseases (76/167, 45.5%), mediation of nearby contact points or test sites (74/167, 44.3%), anonymous medical advice (69/167, 41.3%), and calculation of the risk of having a sexually transmitted disease (63/167, 37.3%) were rated as the most important features. Men were more likely than women to find sexually transmitted disease-related apps useful in general (P=.04; χ2=6.28) and to pay for such apps (P=.01; χ2=9.19). Patients aged <40 years would rather download an app recommended by their physician (P=.03; χ2=7.23), whereas patients aged >40 years preferred reading a patient brochure on sexually transmitted diseases (P=.02; χ2=8.14). - Conclusions: This study demonstrated high general interest in the use of sexually transmitted disease-related apps in this sample of dermatovenereological outpatients. In particular, young age and male sex were significantly associated with a positive perception, underlining the high potential of apps in the prevention and early recognition of sexually transmitted diseases in this group. Future studies are warranted to validate these findings in other populations.